JOSÉ DE LA RIVA-AGÜERO: CENTENARIO DE UNA TESIS MEMORABLE - Coello, Oscar (2005)
In this article, after setting Riva Agüero' s thesis in its right historicalframework, the author describes its contents and assesses its values, acentury ago from dissertation day.